One‐Step Assembly of Visible and Near‐Infrared Emitting Metallacrown Dimers Using a Bifunctional Linker. Issue 5 (13th October 2017) - Nguyen, Tu N.; Chow, Chun Y.; Eliseeva, Svetlana V.; Trivedi, Evan R.; Kampf, Jeff W.; Martinić, Ivana; Petoud, Stéphane; Pecoraro, Vincent L.
Abstract: A family of dimeric Ln III [12‐MCGa(III)N(shi) ‐4] metallacrowns (MCs) (Ln III =Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, and Yb) was synthesized using the isophthalate group (ip 2− ) as a linker. The [LnGa4 ]2 complexes exhibit remarkable photophysical properties, with large molar absorptivities of ≈4×10 4  m −1  cm −1, high quantum yields and long luminescence lifetimes with values of (i) 31.2(2)% and 1.410(1) ms, respectively for the visible‐emitting [TbGa4 ]2 complex and (ii) 2.43(6)% and 30.5(1) μs for the near‐infrared (NIR) emitting [YbGa4 ]2 in the solid state. The NIR emission was obtained not only from Yb, Nd, and Er complexes but also from the less frequently observed emitters such as Pr and Ho. In addition, emission in both visible and NIR domains could be detected for Dy and Sm MCs. ESI‐MS and UV/Vis data revealed that the complexes are highly stable in dimethylsulfoxide (DMSO) solution with the 1 H‐ and COSY‐NMR spectra of the diamagnetic [YGa4 ]2 analogue providing evidence for long‐term solution stability. This new approach allows one to construct a basis for highly luminescent MCs that may be further modified to be adapted for applications such as optical imaging. Abstract : Crowns of many colors : LnGa4 metallacrowns are superior Ln luminescent agents. The use of a bifunctional carboxylate bridging group allows for the isolation of (LnGa4 )2 dimers that retain the high luminescent intensity of the parent but are solution soluble and stable.